2001
DOI: 10.1073/pnas.111551998
|View full text |Cite
|
Sign up to set email alerts
|

Integrated fossil and molecular data reconstruct bat echolocation

Abstract: Molecular and morphological data have important roles in illuminating evolutionary history. DNA data often yield well resolved phylogenies for living taxa, but are generally unattainable for fossils. A distinct advantage of morphology is that some types of morphological data may be collected for extinct and extant taxa. Fossils provide a unique window on evolutionary history and may preserve combinations of primitive and derived characters that are not found in extant taxa. Given their unique character complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
1
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(172 citation statements)
references
References 27 publications
4
159
1
8
Order By: Relevance
“…All species known from Messel used echolocation and were insectivorous (31, 32), but they certainly did not drive the visual mimicry of the leaf insects. Echolocating bats originated and diversified very rapidly during the Early Eocene (33,34), and it has been suggested that the scope of this evolutionary diversification may have been caused by an increase in prey diversity (34). The Eocene insect fauna certainly was very diverse, and the record of a fossil leaf insect presented here is a further indication that much of the former biodiversity of Eocene insects is yet to be discovered.…”
Section: Discussionmentioning
confidence: 83%
“…All species known from Messel used echolocation and were insectivorous (31, 32), but they certainly did not drive the visual mimicry of the leaf insects. Echolocating bats originated and diversified very rapidly during the Early Eocene (33,34), and it has been suggested that the scope of this evolutionary diversification may have been caused by an increase in prey diversity (34). The Eocene insect fauna certainly was very diverse, and the record of a fossil leaf insect presented here is a further indication that much of the former biodiversity of Eocene insects is yet to be discovered.…”
Section: Discussionmentioning
confidence: 83%
“…I used the molecular scaffold approach to determine the most parsimonious position of the fossil plant, because the number of taxa included in the analysis is greater than the number of morphological characters [25]. The tree search was constrained by the relationships among the ANA-grade angiosperms, magnoliids incl.…”
Section: Methodsmentioning
confidence: 99%
“…First, we must recognize that fossil data really are integral to understanding what happened in the past. This prescription is not at all novel (e.g., Doyle and Donoghue, 1987;Novacek, 1996;Springer et al, 2001), but is certainly correct-by finding ways to synthesize fossil and phylogenetic data, we will get the strongest insight on past events. Second, in many cases, the solution is to re-formulate questions so that ancestral character reconstruction is not necessary.…”
Section: Our Ability To Reconstruct Particular Past Events Is Limitedmentioning
confidence: 99%